Oxalyltransferase, a plant cell‐wall acyltransferase activity, transfers oxalate groups from ascorbate metabolites to carbohydrates - Dewhirst, Rebecca A. (Plant J, 2018)
In the plant apoplast, ascorbate is oxidised, via dehydroascorbic acid, to O‐oxalyl esters [oxalyl‐l‐threonate (OxT) and cyclic oxalyl‐l‐threonate (cOxT)]. We tested whether OxT and cOxT can donate the oxalyl group in transacylation reactions to form oxalyl‐polysaccharides, potentially modifying the cell wall. [oxalyl‐(14)C]OxT was incubated with living spinach (Spinacia oleracea) and Arabidopsis cell‐suspension cultures in the presence or absence of proposed acceptor substrates (carbohydrates). In addition, [(14)C]OxT and [(14)C]cOxT were incubated in vitro with cell‐wall enzyme preparations plus proposed acceptor substrates. Radioactive products were monitored electrophoretically. Oxalyltransferase activity was detected. Living cells incorporated oxalate groups from OxT into cell‐wall polymers via ester bonds. When sugars were added, [(14)C]oxalyl‐sugars were formed, in competition with OxT hydrolysis. Preferred acceptor substrates were carbohydrates possessing primary alcohols e.g. glucose. A model transacylation product, [(14)C]oxalyl‐glucose, was relatively stable in vivo (half‐life >24 h), whereas [(14)C]OxT underwent rapid turnover (half‐life ~6 h). Ionically wall‐bound enzymes catalysed similar transacylation reactions in vitro with OxT or cOxT as oxalyl donor substrates and any of a range of sugars or hemicelluloses as acceptor substrates. Glucosamine was O‐oxalylated, not N‐oxalylated. We conclude that plants possess apoplastic acyltransferase (oxalyltransferase) activity that transfers oxalyl groups from ascorbate catabolites to carbohydrates, forming relatively long‐lived O‐oxalyl‐carbohydrates. The findings increase the range of known metabolites whose accumulation in vivo indicates vitamin C catabolism. Possible signalling roles of the resulting oxalyl‐sugars can now be investigated, as can the potential ability of polysaccharide oxalylation to modify the wall's physical properties.